Results of the Mini Clinical Evaluation Exercise applied in the Nursing career. Manabí State University of the South, 2021 - Margoth Elizabeth Villegas Chiriboga; Ismael Morales Ojeda; Marcos Parada Ulloa; Miguel Meriño Morales (Medisur)
Background: in the context of specialties and careers in the health field, it is necessary to implement clinical practice evaluation instruments based on competencies, which meet the required criteria in accordance with their function. Objective: to evaluate the results of the Mini Clinical Evaluation Exercise applied in the evaluation of clinical practices based on competencies for the Nursing career. Methods: comparative study with educational intervention, in which the Mini Clinical Evaluation Exercise was applied as an instrument for evaluating competencies in pre-professional practices of Nursing students, Health Sciences Faculty of the Southern State University of Manabí, in 2021. The Wilcoxon test was used to compare scores. Results: the variables that showed significant differences between the instrument application two moments were the dimensions: attitudes towards patients and the health team (p=0.007) and assessment (p=0.10). Statistically higher scores were observed at the second evaluation moment (p=0.023). The evaluation carried out by the teachers evidenced the improvement of the nursing care process, mainly in terms of guaranteeing the patient's privacy (mean of 7.46). Conclusions: the Mini Clinical Evaluation Exercise is applicable to the context of higher health education in Ecuador. It is verified as an alternative to evaluate competencies in the Nursing career.